2004
DOI: 10.1021/jf035505y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Carotenoids Including Geometrical Isomers in Fruit and Vegetable Juices by Liquid Chromatography with Ultraviolet−Diode Array Detection

Abstract: A method was established for the identification and quantification of carotenoids including geometrical isomers in fruit and vegetable juices by liquid chromatography with an ultraviolet-diode array detector, using a C(18) Vydac 201TP54 column. The mobile phase used was the ternary methanol mixture (0.1 M ammonium acetate), tert-butyl methyl ether and water, in a concentration gradient, and a temperature gradient was applied. Retinol palmitate was added as an internal standard. An extraction process (ethanol/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 48 publications
3
50
2
1
Order By: Relevance
“…Although certain xanthophylls are sensitive to saponification, moderate saponification could be employed. Cortes et al (2004) have shown that 30 min incubation at room temperature with 5 mmol of KOH per sample was sufficient to carry out complete saponification of retinol-palmitate. Consequently, in the present study, our gentle saponification step, in line with those used by others (Association of Official Analytical Chemists 1990; Mercadante and Rodriguez-Amaya 1998;Lee et al 2001), produces a chromatographic profile in agreement with the literature where lutein and the violaxanthin are the xanthophylls mainly found in spinach, followed by b-carotene (Larsen and Christisen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although certain xanthophylls are sensitive to saponification, moderate saponification could be employed. Cortes et al (2004) have shown that 30 min incubation at room temperature with 5 mmol of KOH per sample was sufficient to carry out complete saponification of retinol-palmitate. Consequently, in the present study, our gentle saponification step, in line with those used by others (Association of Official Analytical Chemists 1990; Mercadante and Rodriguez-Amaya 1998;Lee et al 2001), produces a chromatographic profile in agreement with the literature where lutein and the violaxanthin are the xanthophylls mainly found in spinach, followed by b-carotene (Larsen and Christisen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids were extracted and quantified by HPLC, following a procedure validated by Cortés, Esteve, Frígola, and Torregrosa (2004), with some modifications.…”
Section: Carotenoid Compoundsmentioning
confidence: 99%
“…Extracts of citrus fruit peel and pulp are an important and complex source of carotenoids, which are natural pigments, in considerable amounts and in all species. bcryptoxanthin and b-carotene were identified on the basis of comparing their retention times and absorption spectrum characteristics with corresponding authentic standards (Cortés et al, 2004;Bermejo et al, 2011b).…”
Section: Fruit Quality: Nutritional Qualitymentioning
confidence: 99%